2020
DOI: 10.1080/10301763.2020.1723784
|View full text |Cite
|
Sign up to set email alerts
|

The meaning and essential nature of a profession: a multi-perspective approach

Abstract: In the existing literature, there is a lack of consensus among scholars within different research disciplines on the meaning and particularly essential elements of a profession. Consensus would be beneficial to the ongoing debates relating to the notion of a 'profession', and related concepts such as 'professionalisation' and 'professionalism', within the new social systems and organisational work context. To address this limitation of the literature, this paper aims to develop and propose a multidisciplinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…2.2.1 Profession and work. Several authors (Abadi et al, 2020) acknowledge the concept of professions, which was formerly identified as work; this term has arisen with the emergence of industrial society and the division of labour. One of the main characteristics of the 20th century was the development of professions (Evetts, 2012).…”
Section: Profession Professionalism Professional or Professionalisationmentioning
confidence: 99%
“…2.2.1 Profession and work. Several authors (Abadi et al, 2020) acknowledge the concept of professions, which was formerly identified as work; this term has arisen with the emergence of industrial society and the division of labour. One of the main characteristics of the 20th century was the development of professions (Evetts, 2012).…”
Section: Profession Professionalism Professional or Professionalisationmentioning
confidence: 99%